Alexander Woollcott correspondence - Woollcott, Alexander, 1887-1943.
Letters and notes from Woollcott to Lloyd Paul Stryker, his daughter Kitty, and her aunt Alethea Truax discussing personal matters. Accompanied by a letter (25 October 1968) from the dealer, Mary A. Benjamin, pertaining to the correspondents. Also includes typewritten transcripts of letters (1941) from Woollcott to Edmund Wilson discussing Rudyard Kipling, Arthur Waugh, and other authors.
Typewritten transcripts, in part.
Journalist and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Benjamin, Mary A. -- Correspondence; Kipling, Rudyard, -- 1865-1936.; Stryker, Kitty -- Correspondence; Stryker, Lloyd Paul, -- 1885- -- Correspondence; Truax, Alethea -- Correspondence; Waugh, Arthur, -- 1866-1943.; Wilson, Edmund, -- 1895-1972 -- Correspondence; Authors; Authors; Journalists